Electrochemical 5-exo-dig aza-cyclization of 2-alkynylbenzamides toward 3-hydroxyisoindolinone derivatives. Issue 21 (20th May 2022) - Shi, Zhaojiang; Li, Nan; Wang, Wei-Zhen; Lu, Hao-Kuan; Yuan, Yaofeng; Li, Zhen; Ye, Ke-Yin
Abstract : An electrochemical N-attacked 5- exo-dig radical cyclization of 2-alkynylbenzamides toward the synthesis of biologically relevant 3-hydroxyisoindolinone derivatives has been developed. Abstract : Preparation of biologically relevant 3-hydroxyisoindolinones from readily available 2-alkynylbenzamides is an appealing synthetic approach. However, such kinds of compounds preferably undergo O-attacked 5- exo-dig /6- endo-dig cyclizations. Herein, we report an electrochemically generated amidyl radical proceeding via a highly selective N-attacked 5- exo-dig radical cyclization to form 3-hydroxyisoindolinone derivatives. This reaction features simple operation, good selectivity, and broad substrate scope. Moreover, gram-scale preparation and synthetic elaborations imply the potential applicability of this protocol for the synthesis of diverse isoindolinone derivatives.